Relationships Between Some Morphological Characteristics and the Body Mass Index and the Distance Achieved in Shot Put - Ahmed Abdellatif; Badriya Al-Hadabi (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The purpose of this study was to identify the relationships between some morphological characteristics and the body mass index and the distance achieved in shot put. The sample of this study consisted of twenty-one students from Department of Physical Education at Sultan Qaboos University. Morphological characteristics namely body height, legs length, arms length, trunk length, and body weight. Body mass index was calculated as body weight in kilograms divided by height in meters squared. Distance achieved in shot put also was measured. The collected data were analyzed using the statistical package SPSS and the descriptive statistics were expressed as mean (SD) for each variable, while the simple correlation was carried out to detect the relationships between the morphological characteristics, the body mass index and the distance achieved in shot put. The analysis of the data indicates that the distance achieved in shot put was significantly correlated with body height, legs length, arms length and trunk length, while the distance achieved in shot put was not significantly correlated with body weight and body mass index.